Make your own history : timeless truths from Black American trailblazers - Holland, Joseph H. (Dafina, Kensington Publishing Corp., 2023)
One hundred and twenty Black leaders, innovators, and entrepreneurs share their wisdom and experience across the centuries in Make Your Own History, an inspiring collection of exemplary Black voices--past and present, familiar and unsung--which have the power to guide us today.